Identifikasi Kesehatan dan Keselamatan Kerja (K3)Pada SPBE PTD dengan Menggunakan MetodeJob Safety Analysis (JSA) - Ildhan Rephi Al Razy; Edy Soesanto; Abdullah Rizky Agusman (Jurnal Bhara Petro Energi, 2023)
In the operational activities of the oil and gas industry (oil and gas), Occupational Health and Safety (OHS) is very important. Workers in the oil and gas industry have a great potential risk to occupational health and safety conditions. Companies are required to implement an Occupational Health and Safety system to achieve the goal of zero accident industrial operations. Zero accident is a key factor in managing occupational safety and health (OHS). This research focuses on identifying hazards to the interaction between workers, officers/employees, tools and the environment with research indicators namely Human error, not using PPE, technical accidents. The purpose of this study was to determine employee awareness of Occupational Safety and Health (K3) at SPBE PTD and to determine Job Safety Analysis at SPBE PTD in order to create zero accidents with descriptive qualitative methods using Job Safety Analysis (JSA). The results showed that the total average indicator assessment had a value of 2.318, the total average accident in 2020 had a value of 0.833, the total average accident in 2021 had a value of 0.722, and the total average accident in 2022 had a value of 0.833. From the results of the total average value, it can be interpreted that the PTD SPBE does not have zero accidents.